2022
DOI: 10.3389/fonc.2022.833763
|View full text |Cite
|
Sign up to set email alerts
|

A Prognostic Model of Bladder Cancer Based on Metabolism-Related Long Non-Coding RNAs

Abstract: BackgroundSome studies have revealed a close relationship between metabolism-related genes and the prognosis of bladder cancer. However, the relationship between metabolism-related long non-coding RNAs (lncRNA) regulating the expression of genetic material and bladder cancer is still blank. From this, we developed and validated a prognostic model based on metabolism-associated lncRNA to analyze the prognosis of bladder cancer.MethodsGene expression, lncRNA sequencing data, and related clinical information were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Three independent prognostic factors were identified: age, stage, and risk score. As previously reported, age and stage are prominent risk factors for multiple tumors, including bladder Frontiers in Genetics frontiersin.org cancer (Hu et al, 2022;Lu et al, 2022). Further comparison showed that the model's prediction performance is superior to age and stage, demonstrating its high predictive power.…”
Section: Figuresupporting
confidence: 62%
“…Three independent prognostic factors were identified: age, stage, and risk score. As previously reported, age and stage are prominent risk factors for multiple tumors, including bladder Frontiers in Genetics frontiersin.org cancer (Hu et al, 2022;Lu et al, 2022). Further comparison showed that the model's prediction performance is superior to age and stage, demonstrating its high predictive power.…”
Section: Figuresupporting
confidence: 62%
“…Moreover, lncRNA HEPFAL contributes ferroptosis and suppresses tumor progression by affecting SLC7A11 ubiquitination in hepatocellular carcinoma 50 . LINC00239 suppresses ferroptosis and promotes cancer progression in colorectal cancer by interacting with Keap1 to stabilize Nrf2 51 . Although lncRNA are abnormally expressed in EC and are closely correlated to tumor development and chemotherapy resistance 52 , no studies have reported on lncRNAs promoting EC progression by regulating ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their specific expression and biological functions, there is growing interest in these molecules as potential biomarkers. Several reports have investigated the utility of lncRNAs in the clinical setting, and proposed that they can serve as biomarkers in liquid biopsies for diagnosis, monitoring disease progression and therapeutic response [ [20] , [21] , [22] , [23] , [24] ].…”
Section: Introductionmentioning
confidence: 99%